Glycerol-induced hyperhydration: A method for estimating the optimal load of fluid to be ingested before exercise to maximize endurance performance - Goulet, E. D. B. (The Journal of Strength and Conditioning Research, 2010)
Glycerol-induced hyperhydration (GIH) has been shown to increase endurance performance (EP). However, EP starts declining at a dehydration level >2% body weight (BW). It thus appears that the use of GIH is only required when athletes anticipate that their fluid intake during exercise would not be sufficient to prevent a loss of BW >2%. In such a scenario, the optimal GIH load to be ingested before exercise would correspond to the amount of fluid that cannot be drunk during exercise and that would be just sufficient to keep the dehydration level <2% BW. No method exists enabling the estimation of the most optimal GIH load to be drunk before exercise to optimize EP. Here, such a method comprising 3 easy steps is presented. Step 1 provides a formula allowing users to determine relative exercise-induced dehydration level based on individual BW, exercise time, and estimated hourly sweat rate and fluid consumption during exercise. Step 2 takes into account the result of step 1 and provides a formula allowing determination of the minimal GIH load required before exercise to prevent a loss of BW >2%. Step 3 consists of identifying, among those pre-selected, a GIH protocol that increases body water by at least the amount computed in step 2. This method will remove much of the guesswork involved in the decision-making process of the optimal amount of GIH that should be ingested before exercise by athletes for maximizing EP and will serve as a practical reference tool for all athletes using, and coaches, practitioners, and exercise physiologists recommending the utilization of, GIH as an ergogenic aid.